2016
DOI: 10.20868/ade.2016.3198
|View full text |Cite
|
Sign up to set email alerts
|

Hacia un modelo dinámico para la isla de calor urbana de Madrid = Towards a Dynamic Model for the Urban Heat Island of Madrid.

Abstract: Resumen-Esta investigación se enmarca dentro del proyecto MODIFICA (modelo predictivo -Edificios -Isla de Calor Urbano), financiado por el Programa de I + D + i Orientada a los Retos de la sociedad 'Retos Investigación' de 2013. Está dirigido a desarrollar un modelo predictivo de eficiencia energética para viviendas, bajo el efecto de isla de calor urbano (AUS) con el fin de ponerla en práctica en la evaluación de la demanda de energía real y el consumo en las viviendas. A pesar de los grandes avances que se h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…The UHI effects in 1985 made the center of Madrid 4 • C hotter by comparison with peripheral areas (Román et al, 2017). Furthermore, the study in 2016 has shown that temperature difference could be up to 8 • C during the hot summer of Madrid (Núñez Peiró et al 2016). The green space examined in this study was Parque del Retiro or Retiro Park which, with an area of about 125 ha, is one of the largest parks in the center of Madrid.…”
Section: Measuring Sitesmentioning
confidence: 80%
“…The UHI effects in 1985 made the center of Madrid 4 • C hotter by comparison with peripheral areas (Román et al, 2017). Furthermore, the study in 2016 has shown that temperature difference could be up to 8 • C during the hot summer of Madrid (Núñez Peiró et al 2016). The green space examined in this study was Parque del Retiro or Retiro Park which, with an area of about 125 ha, is one of the largest parks in the center of Madrid.…”
Section: Measuring Sitesmentioning
confidence: 80%
“…The UHI effects in 1985 made the center of Madrid 4°C hotter by comparison with peripheral areas (Romá n López et al, 2017). Furthermore, the study in 2016 has shown that temperature difference could be up to 8°C during the hot summer of Madrid (Núñez Peiró et al 2016). The green space examined in this study was Parque del Retiro or Retiro Park which, with an area of about 125 ha, is one of the largest parks in the center of Madrid.…”
Section: Measuring Sitesmentioning
confidence: 92%
“…Recent studies of the UHI of Madrid has shown this temperature difference to be up to 8ºC (Núñez Peiró et al 2016).…”
Section: Relevance Of the Researchmentioning
confidence: 96%